Respuesta :

Answer : the value of (x - y) is 5

Step-by-step explanation:

To solve the given equation we can use the elimination method

Let ,

1. 3x - 2y = 10

2. 2x - 3y = 15

Multiply equation 1 by 2 by equation 2 by 3

2(3x - 2y = 10)

3(2x - 3y = 15)

The equation becomes,

  • 6x - 4y = 20 ....1
  • 6x - 9y = 45 ....2

Now Subtract equation 1 from 2

-9y -(-4y) = 45 - 20

Solving for y:

-9y + 4y = 25

-5y = 25

Divide both sides by -5,

y = -5

So the value of y = -5.

Now substitute the value of y into the original equation.

Solving for x:

3x - 2y = 10

3x - 2(-5) = 10

3x + 10 = 10

3x = 0

x = 0

We have to find the value of (x - y)

= 0 - (-5)

= 0 + 5

= 5

Hence, the value of (x - y) is 5

ACCESS MORE